Application of the Moran Model in Estimating Selection Coefficient of Mutated CSF3R Clones in the Evolution of Severe Congenital Neutropenia to Myeloid Neoplasia - Dinh, Khanh N.; Corey, Seth J.; Kimmel, Marek (Frontiers in Physiology, 2020)
Bone marrow failure syndromes (BMF) such as severe congenital neutropenia (SCN) are leukemia predisposition syndromes. We focus here on the transition from SCN to a pre-malignant myelodysplastic syndrome (MDS). Stochastic mathematical models have been conceived, which attempt to explain the transition of SCN to MDS, in the most parsimonious way, using extensions of standard processes of population genetics and population dynamics such as the branching process and the Moran process. Specifically, in a previous paper, we presented a hypothesis of the SCN → MDS transition, which involves directional selection and recurrent mutation, to explain the distribution of ages at onset of MDS or AML. Based on experimental and clinical data and a model of human hematopoiesis, a range of probable values of the selection coefficient s and mutation rate μ have been determined. These estimates lead to predictions of the age at onset of MDS or AML, which are consistent with the clinical data. In the current paper, based on data extracted from published literature, we seek to provide an independent validation of these estimates. We proceed with two purposes in mind. First, to determine the ballpark estimates of the selection coefficients and verify their consistency with those previously obtained. Second, to provide possible insight into the role of recurrent mutations of the G-CSF receptor in the SCN to MDS transition.